Patent foramen ovale screening and prevention of decompression sickness in divers. (25th November 2020) - Honek, J; Tomek, A; Sefc, L; Horvath, M; Fiedler, J; Sramek, M; Honek, T; Januska, J; Veselka, J
Abstract: Background/Introduction: Patent foramen ovale (PFO) is associated with increased risk of decompression sickness (DCS) due to paradoxical embolization of nitrogen bubbles that form during and after ascent. Screening for PFO using transcranial Doppler ultrasonography (TCD) is currently not recommended for all divers. If a diver is diagnosed with a high-grade PFO and wishes to continue diving there are currently two options to reduce the risk of DCS: catheter-based PFO closure or recommendation of conservative approach to diving. However, to date the evidence for the long-term effectiveness of these measures is limited. Purpose: This study sought to compare the effectiveness of catheter-based PFO closure and conservative diving in the reduction of DCS incidence in divers with a high-grade PFO. Methods: A total of 829 consecutive divers (35.4±10.0 yrs, 81.5% males) were screened for PFO between January 2006 and December 2018 by means of TCD. All patients were prospectively included in the study registry. Patients with a high-grade PFO were offered either catheter-based PFO closure (closure group) or advised to dive within the limits of recreational diving (conservative group). A trans-telephonic follow-up was performed at the end of the study. In this study we compared the incidence rate of DCS prior to enrollment and during the follow-up period in the closure and conservative group. Results: Follow-up was available in 748 (90%) divers. Mean follow-up was 6.5±3.5 years. There were a total of 154 divers with a high-grade PFO that continued diving after the initial screening examination. Fifty-five (36%) of them underwent a catheter-based PFO closure (closure group), the remaining 98 divers were advised to dive within the limits of recreational diving (conservative group). The 55 divers in the closure group performed a total of 63, 436 dives (30, 684 prior to enrollment and 32, 752 during the follow-up). Prior to enrollment there were 108 DCS episodes in 33 divers (incidence rate 3.3/1000 dives) and none during follow-up (p<0.001). The 98 divers in the conservative group performed a total of 48, 069 dives (25, 328 prior to enrollment and 22, 741 during follow-up). There were 91 DCS episodes in 33 divers (incidence rate 3.6/1000 dives) prior to enrollment and 19 episodes in 11 divers (incidence rate 0.75/1000 dives) during follow-up (p<0.001). The incidence rate of DCS was similar for both groups prior to enrollment (p=0.196) but lower in the closure group during the post-interventional follow-up (p<0.001). Conclusion(s): In divers with a high-grade PFO both strategies decreased the incidence rate of DCS. Catheter-based PFO closure was more effective than conservative approach. The results also suggest that divers might benefit from screening for PFO. Funding Acknowledgement: Type of funding source: None